Analytical Studies of Cu(II), Ni(II) and Pd(II) Complexes with 3-Phenyl-Quinazolin-4(3H)-one-2-Carboxaldehydoxime - Singh, K.M.; Kumari Pandey, Bharti (Asian Journal of Chemistry, 2010)
3-Phenyl quinazolin-4-(3H)-one-2-carboxaldehydoxime forms water insoluble chelates with Cu(II), Ni(II) and Pd(II). It has been found to be a selective reagent for the gravimetric estimation of these metal ions in presence of many interfering ions. All the chelates have 1 : 2 (metal : ligand) stoichiometry as shown by Job's method of continuous variation and elemental analysis. Structures of the metal chelates have been established on the basis of magnetic measurements, visible and IR spectra.